Utilization of Kepel (Stelechocarpus burahol) Leaf Extract as a Feed Additive in Broiler Chicken Feed - Mustawa, Adi Ageng; Widjastuti, Tuti; Rusmana, Denny (Jurnal Ilmu Ternak Universitas Padjadjaran, 2023)
This study aims to determine the best level of Kepel leaf extract (Stelechocarpus burahol) used in feeds based on the amount of Escherichia coli in excreta, ileal villi, protein digestibility, ration consumption, and body weight gain (BWG) of broiler chickens. The research was conducted experimentally using a completely randomized design (CRD), four levels of Kepel leaf extract in rations repeated five times. The Kepel leaf extract (EDK) levels used consisted of P 0 = basal ration, P 1 = P 0 + 0.15% EDK, P 2 = P 0 + 0.30% EDK and P 3 = P 0 + 0.45% EDK. Parameters observed were the amount of E. coli in the excreta, ileal villi, protein digestibility, ration consumption, and PBB of broiler chickens. Data were processed using analysis of variance, and if the results were significantly different, then Duncan's test was carried out. The results showed that adding a 0.30% Kepel leaf extract to the feed significantly affects (p<0.01) the number and width of ileal villi and increases protein digestibility. However, it had no significant effect (p>0.05) on the number of E. coli on broiler chickens' excreta, villi height, ration consumption, and BWG.